2018
DOI: 10.5114/cipp.2018.80200
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural studies on the prevalence of personality disorders

Abstract: This article reviews cross-cultural research on personality disorders. The concept of personality disorders is discussed in terms of whether they are universal phenomena or specific to Western society. Then, research on the prevalence of personality disorders in North America, South America, Europe, Asia, Africa, and Australia is reviewed. The overall rates of the prevalence of personality disorders range from 2.40% to 20.00%. The data document that the prevalence of borderline and obsessive-compulsive persona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 85 publications
(91 reference statements)
2
17
1
2
Order By: Relevance
“…Individuals also differ with respect to the behavioral strategies employed to achieve these goals. Learned behavioral strategies and self-regulation reflect parenting and culture such that an evaluation of strategies must take these into account (Gawda, 2018).…”
Section: Behavioral Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals also differ with respect to the behavioral strategies employed to achieve these goals. Learned behavioral strategies and self-regulation reflect parenting and culture such that an evaluation of strategies must take these into account (Gawda, 2018).…”
Section: Behavioral Systemsmentioning
confidence: 99%
“…Themes related to the four questions are found throughout this volume. Gawda (2018) discussed the cross-cultural prevalence of personality disorders in the context of evolutionary psychology and question 3. Differences in prevalence rates were found in individualistic verses collectivistic societies.…”
Section: Tinbergen's Four Questionsmentioning
confidence: 99%
“…To know whether a psychological phenomenon occurs across cultures is important for understanding the interplay between individuals and their cultural context [ 14 , 15 ]. In this line of research, previous studies have suggested that rates of antisocial behavior and related symptoms appear to be more common in individualistic and industrialized cultures than in collectivistic cultures, that is in cultures that prioritize the needs of an individual over the needs of a group as a whole [ 15 , 16 ]. However, other studies did not identify this pattern clearly, and suggest that income inequality could be responsible of higher antisocial behavior and violence by country [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we aim to investigate all types of personality disorders and their relationship to romantic love in prisoner population. This is because this population is thought to present a high occurrence of personality disorders (Gawda, 2018;Tyrer, Mulder, Crawford, Newton-Howes, Simonsen, Ndetei, Barrett, 2010). Related data suggest that approximately 65% of male prisoners are diagnosed with at least one personality disorder, including 47% with antisocial PD, while 42% of female prisoners are diagnosed with a PD, including 21% with antisocial PD (Fazel, Danesh, 2002, p. 545).…”
Section: Introductionmentioning
confidence: 99%